Simulated Acidic Weathering of “Black Granites”: an Assessment using Regression Analysis - Cavalcanti, Ely Brasil de Arruda Luna; Nogueira Neto, José de Araújo; Menor, Eldemar de Albuquerque; da Silva Filho, Adejardo Francisco; da Silva, Marcelo Reis Rodrigues; Amorim, Lucas Fontenele (Anuário do Instituto de Geociências, 2023)
A number of “black granites” were tested using simulated acidic weathering (H2SO4, HNO3, H2SO4/HNO3 and HCl, at pH = 3,00), freeze resistance and relative loss of brightness. The same plates of these granites remained immersed in each acidic solution over eight weekly cycles. The pH data from residual acid solutions were plotted versus timing of the experimental cycles in XY diagrams for interpretation as log-linear regressions. The global set of data, transcribed in a ternary diagram, shows a distinctive area highlighting the best commercial granites. In addition to these granite coatings, the proposed methodology allows easy and accurate identification of their best performances.